CAPACITY OF THE CHILD FORUM IN ADVOCATING CHILD INTERESTS IN THE CHILD-FRIENDLY CITY PROGRAM IN PADANG CITY - Fadhillah Dzulfiqri; Hidayatul Fajri (Musamus Journal of Public Administration, 2023)
This research was conducted with the aim of knowing the capacity of the children's forum in advocating for children's interests in the child-friendly city program in Padang City, as well as the obstacles and constraints experienced by the children's forum in advocating for children's interests in the child-friendly city program in Padang City. This research was conducted using a descriptive qualitative research method. The results showed that the advocacy activities carried out by FORANDANG were socialization of child rights and protection, child rights and protection campaigns, FGDs about fulfilling children's rights and protection, as well as hearings about fulfilling children's rights and protection. The results showed that, FORANDANG did not yet have the capacity to advocate the interests of children in the KLA program, because there are still several categories that have not been fulfilled, such as human resource capacity, financial capacity, and network and relationship capacity. Meanwhile, in terms of carrying out advocacy activities, several obstacles were found, such as a lack of human resources, insufficient funds and difficulty obtaining permits to carry out activities.